Interleukin-1 Blockade in Polygenic Autoinflammatory Disorders: Where Are We now? - Malcova, Hana; Milota, Tomas; Strizova, Zuzana; Cebecauerova, Dita; Striz, Ilja; Sediva, Anna; Horvath, Rudolf (Frontiers in Pharmacology, 2021)
Polygenic autoinflammatory diseases (AIDs), such as systemic juvenile idiopathic arthritis (sJIA), adult-onset Still's disease, Kawasaki disease, idiopathic recurrent pericarditis (IRP), Behçet’s Syndrome, Crystal-induced arthropatihes such as gout or Calcium pyrophosphate deposition disease are characterized by the overexpression of inflammasome-associated genes, leading to a dysregulation of the innate immune response. The IL-1 cytokine family (IL-1α, IL-1β, IL-1Ra, IL-18, IL-36Ra, IL-36α, IL-37, IL-36β, IL-36g, IL-38, IL-33) was defined to be principally responsible for the inflammatory nature of polygenic AIDs. Several clinical trials were initiated, and IL-1 blockade has been proven to cause a rapid reduction of clinical symptoms and normalization of laboratory parameters in the majority of cases. Randomized, placebo-controlled, clinical trials, together with registry-based clinical trials and open-label, retrospective and prospective observational studies, supported the efficacy and safety of IL-1 inhibitors in the treatment of polygenic AIDs. Most of the current data are focused on the therapeutic use of anakinra, an IL 1 receptor antagonist, canakinumab, an anti IL 1β monoclonal antibody, and rilonacept, a soluble decoy receptor. However, other promising agents, such as gevokizumab, IL-1β blocking monoclonal antibody, tadekinig alfa, a human recombinant IL-18-binding protein, and tranilast, an analog of a tryptophan metabolite, are currently being tested. Anakinra, canakinumab and rilonacept caused impressive improvements in both systemic and musculoskeletal symptoms. Furthermore, the anti-IL-1 therapy allowed corticosteroid tapering and, in some cases, even withdrawal. This article reviews the current IL-1 inhibitors and the results of all clinical trials in which they have been tested for the management of broad spectrum of polygenic AIDs.